2012
DOI: 10.1371/journal.pone.0033572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SMN Protein, Transcript, and Copy Number in the Biomarkers for Spinal Muscular Atrophy (BforSMA) Clinical Study

Abstract: BackgroundThe universal presence of a gene (SMN2) nearly identical to the mutated SMN1 gene responsible for Spinal Muscular Atrophy (SMA) has proved an enticing incentive to therapeutics development. Early disappointments from putative SMN-enhancing agent clinical trials have increased interest in improving the assessment of SMN expression in blood as an early “biomarker” of treatment effect.MethodsA cross-sectional, single visit, multi-center design assessed SMN transcript and protein in 108 SMA and 22 age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
138
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 135 publications
(172 citation statements)
references
References 55 publications
(48 reference statements)
19
138
1
2
Order By: Relevance
“…Very recently, some of us (FDT and LR) have collaborated to the BforSMA study. 39,40 Also in that large cohort of young patients spanning the whole phenotypic spectrum of the disease, SMN2-fl levels were significantly higher in the less severely affected subjects, although they were not predictive of the motor performance of single individuals. We found similar results also in our previous study.…”
Section: Discussionmentioning
confidence: 88%
“…Very recently, some of us (FDT and LR) have collaborated to the BforSMA study. 39,40 Also in that large cohort of young patients spanning the whole phenotypic spectrum of the disease, SMN2-fl levels were significantly higher in the less severely affected subjects, although they were not predictive of the motor performance of single individuals. We found similar results also in our previous study.…”
Section: Discussionmentioning
confidence: 88%
“…Correlation analysis revealed that there was no association between SMN2 CGIs methylation levels and total SMN2 transcript levels (SMN2-fl+SMN2-7) (Crawford et al, 2012). However, 3/8 differentially methylated CpG units correlated with different SMN2 transcripts after applying a Bonferroni correction (P<0.017).…”
Section: Smn2 Cgis Methylation Frequencies and Transcript Levelsmentioning
confidence: 91%
“…Aligned with therapeutic approaches designed to increase SMN levels, efforts to develop candidate biomarkers have also concentrated on measurement of SMN protein expression. While this can reliably be measured in peripheral blood and relates to SMA type, SMN protein levels do not predict severity of motor function, and it remains to be determined if this reflects what is happening in motor systems [126,127]. Development of non-SMN molecular biomarkers using proteomic, metabolomics, and transcriptomic approaches holds promise for SMA, even though these measures may not be able to distinguish primary (initiating) and secondary (responsive) changes in gene expression.…”
Section: Challenges Is Smn1-related Sma Therapeuticsmentioning
confidence: 99%